PENGARUH PEMBERIAN ANTIBODI POLIKLONAL PMSG (Pregnant Mare Serum Gonadotropin) (Abpo PMSG) YANG BERASAL DARI KELINCI (Oryctolagus cuniculus) JANTAN TERHADAP JUMLAH FETUS MENCIT (Mus musculus) - rahmawati, indra (Jurnal Ilmiah Kedokteran Wijaya Kusuma, 2018)
The purpose of this study was to evaluate the potencial influence local product Abpo PMSG treatment on mice foetus number. Methode used for this research was by injecting 0,1 ml Abpo PMSG on superovulated mice with PMSG and hCG. There were six treatment in this research. Control group was groupÂ  of mice that only superovulated. P1 was given PMSG and Abpo PMSG together. P2 was group of mice that wich Abpo given 1 hour after PMSG, P3 given Abpo PMSG when they were estrous. P4 given Abpo PMSG 1 hour before hCG, and P5 given Abpo PMSG 1 hour after hCG. The result showed that the most foetus number resulted from P3. The least foetus number was from control group. Foetus number of P1, P2, P4 and P5 was showed no significant difference with P3 group ( P > 0,05).Key words : PMSG, Abpo PMSG, foetus number